Специфика речевого воздействия в рекламе (на примере российских женских журналов) - Wasiluk, Joanna (Acta Polono-Ruthenica, 2019)
This article analyses advertising texts published in the Russian magazines for women and indi-cates the importance of the selection of appropriate graphics and lexical means (including word-for-mation). The aim of the analysis is to present the typology of linguistic means which are most commonly used in advertising texts, especially considering the contemporary of life in society. Cur-rently, we increasingly feel the lack of time and we are bombarded by new objects and concepts that appear at almost every step. The creators of advertising texts try to attract the attention of consumers in a variety of ways, so as to encourage them to buy goods. The big, if not the leading role is played by the language of advertising, which is reflected in the various forms of play on words as well as in the form of newly created words.